Development of a counter - top thermoacoustic demonstrator [electronic resource] - 423118 Jerry Ajeng (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2007